STUDI NUMERIK UMUR KELELAHAN (FATIGUE LIFE) PADA PROPELLER KAPAL PENANGKAP IKAN DENGAN KAPASITAS MESIN 24 HP - Rizqi Ilmal Yaqin; Angger Bagus Prasetiyo; Pritiansyah Pritiansyah; Muhammad Haritsah Amrullah; Binsar Maruli Tua Pakpahan (Jurnal Teknologi Terapan, 2020)
Propeller is part of a key component in fishing boat propulsion. Propeller can provide momentum to the fluid which can be a thrust on the ship. However, The failure of the propeller found prematurely. The failure of the propeller maybe because of overload on the propeller model so the fatigue life of the propeller becomes low. On the other hand, the rapid development of technology can simulate a design model to look for failures that occur. Finite Element Analysis is one of the designer solutions to determine the age of failure of a model and failure-prone areas in a model. This study uses propeller model data from fishing boat with engine 24HP in Dumai City TPI that always fail prematurely. The material used is copper alloy. While the drawing model uses Autodesk Inventor and Finite Element Analysis simulation using ANSYS R17.2 software with the number of model nodes is 51108 and the number of elements of the model is 26268. The results obtained from this study are Von Mises stress on the simulation model that is equal to 613.33 MPa to 0.01164 MPa. While the deformation value due to the effect of loading on the model is 5,3657 mm to 0 mm. These results affect the age of fatigue (fatigue life) on the model with the highest value 109 and the lowest 0. The results of the fatigue life value on the model affect the results of the level of damage and the safety number of the model with successive values of 1032 to 1 and 15 to 0.32446. The conclusion of the result is the propeller will fail prematurely.